PERHITUNGAN KOMPARASI ENERGI BAHAN BAKAR SEKAM PADI DENGAN MINYAK TANAH - Purwo Subekti (Universitas Pasir Pengaraian, 2012)
Utilization of rice husk as a fuel substitute alternativ kerosene using rice husk stove is a technology based on local wisdom to anticipate the threats of energy crisis, as one of the replacement of fuel oil. Comparative analysis of rice husk stove with kerosene stove will produce a comparison of how the conclusions, ability and energy efficiency in cooking. From the analysis of the efficiency of kerosene stove showed a better value than a stove fueled by rice husks. However, the ability of rice husk energy as an alternative fuel in a fuel oil substitute very effectively developed for household, small and medium industries, especially in rural areas, it is based on the price of rice husk is much cheaper than kerosene.